2009
DOI: 10.1071/rj09005
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities and limitations of food - feed crops for livestock feeding and implications for livestock - water productivity

Abstract: The paper discusses the contribution of crop residues (CR) to feed resources in the context of the water productivity of CR in livestock feeding, using India as an example. It is argued that crop residues are already the single most important feed resource in many livestock production systems in developing countries and that increasing their contribution to livestock feeding needs to be linked to improving their fodder quality. Using examples from multi-dimensional crop improvement, it is shown that CR fodder … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 1 publication
0
19
0
Order By: Relevance
“…They are also home to a diverse range of wildlife that includes antelopes, giraffes, rhinos, lions, and some of the largest populations of elephants in Africa [5]. However, over the years, these ecosystems have experienced vast changes in their physical nature, which affect the roles they play as a result of land degradation caused by humans who clear land for cultivation [3]. Land degradation manifests itself in many forms, and the common way is through the transformation of the land from its natural state into man-made land use forms, e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are also home to a diverse range of wildlife that includes antelopes, giraffes, rhinos, lions, and some of the largest populations of elephants in Africa [5]. However, over the years, these ecosystems have experienced vast changes in their physical nature, which affect the roles they play as a result of land degradation caused by humans who clear land for cultivation [3]. Land degradation manifests itself in many forms, and the common way is through the transformation of the land from its natural state into man-made land use forms, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Land use change is often the first consequence of population and economic growth, and it can be argued that low soil fertility, lack of infrastructure, and the presence of diseases have been the main factors preserving miombo [3,7,19]. However, due to increased demand for land for cultivation, a new dimension was created leading to massive land cover changes and degradation.…”
Section: Introductionmentioning
confidence: 99%
“…soil nutrient and associated crop yield) on livestock are manifold: (1) low feed availability because of low biomass productivity; (2) low feed quality associated with multi-nutrient deficiencies (Gowda et al 2004). Blümmel et al (2009b) also suggested that as a compensation for low feed quality, livestock's total dry matter demand can be higher, and this puts additional pressure on the already feed-deficit farming systems and thus hampers efforts made by the international and local communities to take advantage of the development opportunity offered by the global 'livestock revolution' [e.g. increasing demand for livestock products (Steinfeld et al 2006)].…”
Section: Introductionmentioning
confidence: 99%
“…The screening of a wide range of cultivars of rice, wheat, maize, sorghum, pearl millet, cowpea, groundnut, pigeon pea and chickpea has shown that differences of 3-5% units in digestibility can be exploited without detriment to grain yield (Blümmel et al, 2009c). Conventional and molecular breeding techniques for improving the food and feed traits simultaneously are more expensive but have higher impact potential because full genetic crop variability can be explored and utilized .…”
Section: Technologiesmentioning
confidence: 99%